Efektivitas pemberian makanan bergizi untuk peningkatan berat badan pada balita - Kumalasari, Dian; Wulandari, Umianita Risca (Jurnal Kebidanan, 2025)
Stunting is a condition of chronic malnutrition resulting from a lack of nutritional intake that begins over a long period of time, usually caused by the food intake provided not being in accordance with the nutritional needs of the child. Parenting patterns in providing food are an important factor in fulfilling toddlers' nutritional needs. Therefore, this study aims to measure the effectiveness of providing food with weight gain in toddlers. The design of this study was quasi-experimental with one group pre-post with a sample size of 20. Sampling technique with total sampling. Research instruments using questionnaires and checklists. Data analysis using paired t-test. The results of the study showed that the p value = 0.001 (<0.005) so that Ha was accepted so that providing food increased the weight of toddlers. Keywords: nutritious food, weight, toddler